Hobbes’s Literary Technology of the Commitment to Reason - Maršálek, Jan (Teorie vědy / Theory of Science, 2017)
Does a perfectly established proof also imply, for its beholder, a commitment to account for the proof’s conclusion in further reasoning and action? In the herein presented study, I treat Thomas Hobbes’s Leviathan as a “literary technology” that seeks to position the reader into the role of the author in Leviathan’s argumentation. The interpretations of Hobbes’s scientific style offered by S. Shapin and S. Schaffer are thus critically developed alongside Q. Skinner’s analysis of Hobbes’s rhetorical practice. It is suggested that, with regard to his readers, Hobbes does not content himself with merely demonstrating a scientific proof, but strives to involve his readers in his argumentation and make them participate in the creation of scientific arguments and their conclusions.